2015
DOI: 10.1002/2015jd023193
|View full text |Cite
|
Sign up to set email alerts
|

Frozen soil degradation and its effects on surface hydrology in the northern Tibetan Plateau

Abstract: Frozen soil was simulated at six seasonally frozen and seven permafrost stations over the northern Tibetan Plateau using the Variable Infiltration Capacity (VIC) model for the period of 1962-2009. The VIC model resolved the seasonal cycle and temporal evolution of the observed soil temperatures and liquid soil moisture well. The simulated long-term changes during 1962-2009 indicated mostly positive trends for both soil temperature and soil moisture, and negative trends for soil ice content at annual and monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 69 publications
7
85
0
Order By: Relevance
“…This study also showed that the thawing of frozen soils increased the liquid soil moisture in the upper Heihe basin, which is consistent with the finding of Subin et al (2013) using the CLM to simulate northern high-latitude permafrost regions, and the findings of Cuo et al (2015) using the VIC model to simulate 13 sites on the QTP. In contrast, Lawrence et al (2015) found that permafrost thawing reduced soil moisture based on CLM simulations of the global permafrost region.…”
Section: Comparison With the Previous Similar Studiessupporting
confidence: 78%
See 1 more Smart Citation
“…This study also showed that the thawing of frozen soils increased the liquid soil moisture in the upper Heihe basin, which is consistent with the finding of Subin et al (2013) using the CLM to simulate northern high-latitude permafrost regions, and the findings of Cuo et al (2015) using the VIC model to simulate 13 sites on the QTP. In contrast, Lawrence et al (2015) found that permafrost thawing reduced soil moisture based on CLM simulations of the global permafrost region.…”
Section: Comparison With the Previous Similar Studiessupporting
confidence: 78%
“…Subin et al (2013) and Lawrence et al (2015) used the CLM to simulate global changes in permafrost. Cuo et al (2015) used the VIC to simulate frozen soil changes and their hydrological impacts on the plot scale in the headwaters of the Yellow River. The GEOtop model (Endrizzi et al, 2014) simulates three-dimensional water flux and vertical heat transfer in soil, but it is difficult to apply to regional investigations.…”
Section: Introductionmentioning
confidence: 99%
“…For precipitation, only the amount but not the frequency is changed. These scenarios bear similarity to what has been identified over the NTP in recent decades in general in that S1 plus S2, S3, S4 and S5 represent regional frozen soil degradation, warming, wetting and elevated CO 2 trends, respectively, although the rates of changes and spatial patterns differ (Cuo et al, 2013b(Cuo et al, , 2015. Uniform perturbations are introduced to provide the benchmark for the climate sensitivity comparison across the region and to derive sensitivity spatial pattern.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Jin et al (2013) found that spatial patterns and temporal trends of phenology were parallel with the corresponding soil physical conditions over the TP, and that 1 • C increase in soil temperature could advance the start of the growing season by 4.6-9.9 days. On the TP where a vast area of seasonally frozen (SFS) and permafrost (PFS) soil exists (Cheng and Jin, 2013), global warming induced frozen soil degradation (Cuo et al, 2015) could potentially affect litter decomposition and plant phenology .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation